Volume 3A: 48th Design Automation Conference (DAC) 2022
DOI: 10.1115/detc2022-90246
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Characterization of Lattice, Spring, and Non-Assembly Mechanisms Fabricated With Nylon Polymer Powder Bed Fusion

Abstract: Emerging additive manufacturing technologies are enabling the design of engineered parts with complex geometries and mechanical capabilities. Polymer powder bed fusion (PBF) printing is a promising process that is becoming more economically accessible while providing capabilities for printing non-assembly mechanisms. These processes could enable the automated design of complex personalized biomedical designs, such as prosthetics with integrated lattices, springs, and joints. However, manufacturing constraints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Powder printing processes are particularly useful for non-assembly mechanism creation since unused powder is present in areas between components of joints that, once removed, enables the movement of mechanisms requiring no further assembly. A recent study on nylon-powder-printed prosthetics found that relevant mechanisms operated best within a specified range of gap sizes from about 0.2 to 0.4 mm [13]. Further studies with geometric tolerances of laser powder bed fusion found that 15 mm diameter holes had mean printed diameters of 15.05 and 15.03 mm with standard deviations of 0.04 mm [54].…”
Section: Constraintsmentioning
confidence: 96%
See 4 more Smart Citations
“…Powder printing processes are particularly useful for non-assembly mechanism creation since unused powder is present in areas between components of joints that, once removed, enables the movement of mechanisms requiring no further assembly. A recent study on nylon-powder-printed prosthetics found that relevant mechanisms operated best within a specified range of gap sizes from about 0.2 to 0.4 mm [13]. Further studies with geometric tolerances of laser powder bed fusion found that 15 mm diameter holes had mean printed diameters of 15.05 and 15.03 mm with standard deviations of 0.04 mm [54].…”
Section: Constraintsmentioning
confidence: 96%
“…A table is provided at the end of the section that highlights the relevant materials and processes for each application area considered. [95], (B) a lightweight steering wheel [96], (C) bridge construction [97], (D) a chocolate printed geometry [98], (E) a finger prosthetic [13], and (F) a soft tensegrity robot [99]. Images adapted with permission.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations